Reaching the Top? Profiles of Impression Management and Career Success - Maike E. Debus; Pia V. Ingold; Christian Gross; Mark C. Bolino (Journal of Business and Psychology, 2024)
Abstract Employees use impression management (IM) tactics to influence their image at work. Whereas findings regarding the effects of IM on interview outcomes and performance evaluations are extensive, our understanding of the career implications of IM is both limited and inconclusive. In this two-study paper, we used latent profile analysis to better understand the relationship between the use of five IM tactics in combination—ingratiation, self-promotion, exemplification, intimidation, and supplication—and multiple indicators of objective career success (i.e., salary, promotions, and supervisor-rated reward recommendations) and subjective career success. Four different IM profiles were identified in a sample of 237 employees in Study 1 and which were replicated in Study 2 with 268 employees. In Study 1, we found that the highest levels of salaries and promotions (reflecting objective career success) were associated with a passive use of IM (i.e., employing all five IM strategies at low frequency), thereby running counter to our initial expectations. In contrast, the highest level of subjective career success was associated with a positive use of IM (i.e., a pattern employing the three positive strategies ingratiation, self-promotion and exemplification at higher levels). In Study 2, we found positive use of IM to be associated with the highest level of supervisor-rated reward recommendations as a further indicator of objective career success (followed by passives with the second highest reward recommendations). Our findings highlight the importance of viewing objective and subjective career success as qualitatively different constructs and suggest benefits of employing passive IM use for objective career success.
Keywords: 330; Impression management; Latent profile analysis; Reward recommendation; Career success